New perspectives in service-learning : research to advance the field - Welch, Marshall; Billig, Shelley (Emerald Publishing Limited : Information Age Pub., 2004)
This installment in the book series "Advances in Service-Learning Research", edited by Shelley H. Billig and Marshall Welch, focuses on New Perspectives in Service-Learning.
Selected papers from the Third Annual International K-H Service-Learning Research Conference that took place in November 2003 in Salt Lake City, Utah.
Keywords: Service learning -- Congresses.; Service learning -- Research -- Congresses.; elektronické knihy; Conference papers and proceedings.; Education -- General.; Education.; electronic books